A genetic toolkit and gene switches to limit Mycoplasma growth for biosafety applications - Alicia Broto; Erika Gaspari; Samuel Miravet-Verde; Vitor A. P. Martins dos Santos; Mark Isalan (Nature Communications, 2022)
Mycoplasmas are minimal cell model organisms but lack genetic tools. Here the authors provide a robust genetic toolkit for Mycoplasma demonstrating gene circuit engineering applications.